2018
DOI: 10.1016/j.ophtha.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Progression of Myopic Maculopathy

Abstract: The 10-year progression rate of myopic maculopathy in this elderly Chinese population was 35.5%, increasing from 15 of 79 eyes (19%) in category 1 of myopic maculopathy at baseline to 17 of 24 eyes (71%) in category 2 and 6 of 6 eyes (100%) in category 3. Risk factors for myopic maculopathy progression were longer axial length, pre-existing staphylomata, smaller parapapillary γ-zone, older age, and female gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
108
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 37 publications
14
108
3
3
Order By: Relevance
“…We found no association between MMD progression and age, which contrasts with some studies that reported increased risk of MMD progression with older age, 16,17 but were consistent with others, such as the Beijing Eye Study and Handan Eye Study. 7,15 The lack of association between MMD progression and age may be due to the small number of patients with MMD progression and short follow-up period of 5 to 6 years compared with studies that found a significant relationship, which had longer follow-up periods of at least 10 years.…”
Section: Risk Factors For MMD Progressionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found no association between MMD progression and age, which contrasts with some studies that reported increased risk of MMD progression with older age, 16,17 but were consistent with others, such as the Beijing Eye Study and Handan Eye Study. 7,15 The lack of association between MMD progression and age may be due to the small number of patients with MMD progression and short follow-up period of 5 to 6 years compared with studies that found a significant relationship, which had longer follow-up periods of at least 10 years.…”
Section: Risk Factors For MMD Progressionsupporting
confidence: 84%
“…a 10-year incidence of MMD at 19.0% in 79 highly myopic eyes of Chinese adults. 16 However, this study reported MMD changes among highly myopic adults only and did not consider individuals with low or moderate myopia who are also at risk of developing MMD. 11 In population-based studies, the 5-year progression rate of MMD ranged from 15.1% to 35.3%, 6,7,15 and the 10-year progression rate was reported to be 77.4% of eyes with MMD.…”
mentioning
confidence: 96%
“…Recently, several studies have reported that the development or enlargement of PPA was a risk factor for the progression of myopic maculopathy, as well as a risk factor for the progression from high myopia to pathologic myopia. 37,38 Although most young myopic patients in the present study did not yet have myopic maculopathy, choroid thinning has been observed, especially in those with larger PPA area. With the progression of myopia, especially severe myopia, the deformation of the eyeball is gradually aggravated, the ChT in subjects with a larger PPA area is more susceptible to further thinning and subsequent myopic chorioretinal changes may occur.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, many other studies found that most macular atrophy developed from CNV, while development of patchy-related macular atrophy was quite rare. 11,12,21 Patchy atrophy and macular atrophy may be different types of MM rather than a relationship of progress. 23 We also found some CNV-related macular atrophy eyes in which the atrophic lesion was limited, and no obvious atrophic changes were found around the lesion.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 99%
“…[7][8][9] It is estimated that, without changing the current interventions, up to 55.7 million people will have visual impairment, and up to 18.5 million people will be blind, owing to myopic maculopathy (MM) worldwide in 2050. 10 Based on a simplified classification system, known as the International Photographic Classification and Grading System for myopic maculopathy (META-PM), Yan and associates 11 and Fang and associates 12 recently reported the long-term progression pattern of MM in Chinese and Japanese high myopia cohorts, respectively. Both investigators found that the risk factors for MM progression were a longer axial length (AL), older age, and development of parapapillary atrophy (PPA), while Yan further identified pre-existing staphyloma and female sex.…”
mentioning
confidence: 99%